2012
DOI: 10.1515/cclm-2012-0410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of [−2] proPSA and Prostate Health Index (phi) for the detection of prostate cancer: a systematic review and meta-analysis

Abstract: The usefulness of %[ − 2] proPSA and Prostate Health Index (phi) in the detection of prostate cancer are currently unknown. It has been suggested that these tests can distinguish prostate cancer from benign prostatic diseases better than PSA or %fPSA. We performed a systematic review and meta-analysis of the available scientific evidence to evaluate the clinical usefulness of %[ − 2] proPSA and phi. Relevant published papers were identified by searching computerized bibliographic systems. Data on sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
100
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 33 publications
2
100
0
4
Order By: Relevance
“…Whereas, p2PSA was the most stable form in serum. [14] In many studies related to proPSA, rates for tPSA/pPSA, pPSA/ sPSA, pPSA/sPSA/tPSA, and pPSA/BPSA have been determined. For example, Khan et al [32] indicated that in cases with tPSA values ranging between 4, and 10 ng/mL, pPSA levels measured in order to refrain from unnecessary biopsies had 90% sensitivity, and 44% specificity.…”
Section: Propsa (Ppsa)mentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas, p2PSA was the most stable form in serum. [14] In many studies related to proPSA, rates for tPSA/pPSA, pPSA/ sPSA, pPSA/sPSA/tPSA, and pPSA/BPSA have been determined. For example, Khan et al [32] indicated that in cases with tPSA values ranging between 4, and 10 ng/mL, pPSA levels measured in order to refrain from unnecessary biopsies had 90% sensitivity, and 44% specificity.…”
Section: Propsa (Ppsa)mentioning
confidence: 99%
“…In a few studies performed in patients with tPSA levels of 2.5-10 ng/mL, in the discrimination between PCa, and BPH, p2PSA/fPSA ratio was reportedly more meaningful as for detection of PCa relative to tPSA or % fPSA. [14] Naya et al [37] , indicated lack of any significant difference between patients with or without PCa as for pPSA values, and % pPSA within a tPSA interval 4.4-8.5 ng/mL. Catalona et al [38] observed increases in % pPSA values in PCa patients with tPSA values varying between 2, and 10 ng/mL, and stated that % pPSA has higher diagnostic sensitivity, and specificity for PCa when compared with % fPSA without any correlation between histopathological stage, and % pPSA.…”
Section: Propsa (Ppsa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the term derivative may evoke some distrust, in laboratory medicine, in contrast to the financial world, derivative tests are based on solid scientific foundations and are useful in aiding diagnosis. [18]. It has been demonstrated that despite costs associated with the procedure, the utilization of %[-2] proPSA or phi is cost-effective and reduces the global costs.…”
mentioning
confidence: 99%
“…In addition to the review on [-2] proPSA and phi by Filella and Gimenez [ 18 ], other papers in the current issue of Clinical Chemistry and Laboratory Medicine illustrate the philosophy behind tumor marker utilization in the management of prostate cancer as well as other tumors. Two papers address different methodological issues of PSA determination.…”
mentioning
confidence: 99%